Opportunism in Multilateral Vertical Contracting: Nondiscrimination, Exclusivity, and Uniformity - McAfee, R. Preston; Schwartz, Marius (American Economic Review, 1994)
An input supplier selling to competing downstream firms would benefit from publicly committing at the outset to all contracts. Efficient commitment, however, would require complete contracts. We study instead bilateral contracting, without commitment regarding others' terms. Each firm then fears that the supplier might opportunistically renegotiate another's contract to increase bilateral profit at the firm's expense. We show that nondiscrimination clauses generally cannot curb such third-party opportunism, even with symmetric firms. To reassure firms, crude forms of commitment may be adopted. This could explain the pervasiveness of exclusivity arrangements and the striking uniformity and intertemporal rigidity of franchise contracts.